The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.1177/1045389x14533429
|View full text |Cite
|
Sign up to set email alerts
|

Design and development of a novel displacement differential self-induced magnetorheological damper

Abstract: Design and development of a novel displacement differential self-induced magnetorheological damper AbstractThis article presents the development of a novel magnetorheological damper which has a self-sensing ability. In this study, a linear variable differential sensor, which was based on the electromagnetic induction mechanism, was integrated with a conventional magnetorheological damper. The working principle, configuration, and prototype of the displacement differential self-induced magnetorheological damper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 24 publications
(24 reference statements)
0
16
0
Order By: Relevance
“…al. [20] evaluated static and dynamic behaviour of a MR damper with a self-induced capability integrated with a linear variable differential sensorbased. Also, Hu et al [21] proposed a self-sensing MR damper with an electromagnetic harvester with controllable damping capability.…”
Section: Introductionmentioning
confidence: 99%
“…al. [20] evaluated static and dynamic behaviour of a MR damper with a self-induced capability integrated with a linear variable differential sensorbased. Also, Hu et al [21] proposed a self-sensing MR damper with an electromagnetic harvester with controllable damping capability.…”
Section: Introductionmentioning
confidence: 99%
“…Due to its excellent dynamic properties, such as the simple structure, larger damping force, wider adjustable range, fast response, and low power consumption, it is also widely used in bridge construction, military aerospace, and other industrial fields. 8,9 To achieve a larger damping force, many different types of studies have been reported. A three-coil MR damper was developed by Lord Corporation, which can increase the damping force by increasing the effective damping length with maximum 20t load.…”
Section: Introductionmentioning
confidence: 99%
“…Guan et al (2015) proposed a novel compact MR damper with self-powered capability and combined a ball-screw-based generation device, which could act as a velocity sensor in open-circuit state. Hu et al (2015a, 2015b, 2017) proposed a displacement self-induced MR damper structure and a self-sensing in-line coil mechanism; results indicated that both models have the ability to output displacement-dependent voltages and stable damping force simultaneously. Sun et al (2015) developed a self-sensing magnetorheological elastomer (MRE) adaptive tuned vibration absorber and tested the performance of the self-sensing capability from 3 A, 4.8 Hz to 11.3 Hz, and the result showed the absorber has higher efficiency than passive system.…”
Section: Introductionmentioning
confidence: 99%